2023
DOI: 10.3389/fphar.2023.1069093
|View full text |Cite
|
Sign up to set email alerts
|

Crebanine induces ROS-dependent apoptosis in human hepatocellular carcinoma cells via the AKT/FoxO3a signaling pathway

Abstract: Background: Hepatocellular carcinoma (HCC), as an aggressive cancer with a high mortality rate, needs high-efficiency and low-toxicity drug therapy. Natural products have great potential as candidate lead compounds for the development of new HCC drugs. Crebanine is an isoquinoline alkaloid derived from Stephania with various potential pharmacological effects such as anti-cancer. However, the molecular mechanism underlying crebanine-induced liver cancer cells apoptosis has not been reported. Here, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The FOXO transcription factor family consists of FOXO1, FOXO3a, FOXO4 and FOXO6 [21]. Among these, FOXO3a has been extensively investigated compared to the other transcription factors, and it was revealed to play a pivotal role in regulating the expression of numerous genes involved in cell proliferation, cell cycle and apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The FOXO transcription factor family consists of FOXO1, FOXO3a, FOXO4 and FOXO6 [21]. Among these, FOXO3a has been extensively investigated compared to the other transcription factors, and it was revealed to play a pivotal role in regulating the expression of numerous genes involved in cell proliferation, cell cycle and apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to producing proinflammatory factors, the PI3K/Akt pathway has been shown to suppress apoptosis via inactivation of caspase 3/7 and activation of B-cell lymphoma 2 (Bcl-2) protein in head and neck squamous cell carcinomas ( Su et al, 2022 ). Another study on the influence of CB on the hepatocellular carcinoma cell HepG2 showed inhibition of the PI3K/Akt/FoxO3a pathway, possibly inducing the mitochondrial apoptosis pathway ( Tan et al, 2023 ). Our study further demonstrated that CB inhibits the PI3K/Akt pathway and could thus induce apoptosis in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The actuality of CB’s ability to penetrate the BBB also needs to be shown through in vivo experiments. Third, the dosages used in our research, though referenced from published studies, are relatively high ( Cui et al, 2022 ; Tan et al, 2023 ). The toxicity of high-dose CB on normal healthy cells is a significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…ROS can influence cell membrane fluidity and permeability via lipid peroxidation that leads to cell death [4]. Prior research has indicated that ferroptosis can potentially be linked to several types of malignancies, including hepatocellular carcinoma [14], colorectal cancer [15], and gastric cancer [16]. This article outlines the process of ferroptosis in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%